(Z)-3′,6′-Bis(diethylamino)-2-(4-oxopent-2-en-2-ylamino)spiro[isoindoline-1,9′-xanthen]-3-one - Guo, Chang-Bin (International Union of Crystallography, 2012)
In the title compound, C(33)H(38)N(4)O(3), the mean planes of the 9H-xanthene unit and spirolactam (nine-atom) core are almost mutually perpendicular at 87.26 (6)°. Intramolecular N—H⋯O and C—H⋯N interactions influence the 4-oxopent-2-en-2-ylamino conformation. In the crystal, weak C—H⋯O hydrogen bonds link the molecules into chains along [001].